Erectile function in circumcised and uncircumcised men in Lusaka, Zambia: A cross-sectional study - Evans Chinkoyo; Michael Pather (AOSIS, 2015)
Background: Evidence from three randomised control trials in South Africa, Uganda and Kenya showing that male circumcision can reduce heterosexual transmission of human immunodeficiency virus (HIV) infection from infected females to their male partners by up to 60% has led to an increase in circumcisions in most African countries. This has created anxieties around possible deleterious effects of circumcision on erectile function (EF). Aim: To compare EF in circumcised and uncircumcised men aged 18 years and older. Setting: Four primary healthcare facilities in Lusaka, Zambia. Methods: Using a cross-sectional survey 478 participants (242 circumcised and 236 uncircumcised) from four primary healthcare facilities in Lusaka, Zambia were asked to complete the IIEF-5 questionnaire. EF scores were calculated for the two groups, where normal EF constituted an IIEF-5 score ≥ 22 (out of 25). Results: Circumcised men had higher average EF scores compared to their uncircumcised counterparts, (p < 0.001). The prevalence of erectile dysfunction was lower in circumcisedmen (56%) compared to uncircumcised men (68%) (p < 0.05). EF scores were similar in thosecircumcised in childhood and those who had the procedure in adulthood, (p = 0.59). The groups did not differ significantly in terms of age, relationship status, smoking, alcohol and medication use. A statistically significant difference was observed in education levels, with the circumcision group having higher levels of education (p < 0.005). Conclusion: The higher EF scores in circumcised men show that circumcision does not confer adverse EF effects in men. These results suggest that circumcision can be considered safe interms of EF. A definitive prospective study is needed to confirm these findings.